Specimens of Galatheidae (Crustacea: Decapoda) collected by N.Pq. "Soloncy Moura" off the Southern Coast of Brazil under the Revizee Program - de Melo-Filho, Gustavo A. Schmidt (Zootaxa, 2008)
The purpose of this work was to analyze the distribution patterns of the species belonging to the family Galatheidae collected under the Revizee Program (Living Resources in the Exclusive Economic Zone) off the Brazilian Southern Coast. The study area extended from the Baía da Guanabara (Rio de Janeiro; 23°43’S) south to Ilha de Santa Catarina (Santa Catarina; 27°22’S). The collections were made during several cruises of N.Pq. “Soloncy Moura” between August 2001 and April 2002 over the shelf and slope (101–604 m). One species of the genus Agononida, five species of Munida, and one species of Munidopsis were collected. The general distribution patterns of the species are discussed.